ANALISIS KEMAMPUAN BERFIKIR KRITIS SISWA VII SMP MENGGUNAKAN MODUL POE BERBASIS ESD PADA MATERI LISTRIK STATIS - Umi Fatimah, Fahrun Nisa; Siswanto, Joko (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2022)
The lack of references to teaching modules used by teachers to carry out learning is one of the problems in learning in SMP Muhammadiyah Lasem. This study aims to determine the effect of learning modules. The population used in the study was class VII SMP Muhammadiyah Lasem consisting of 10 students who were used as samples in the study. Retrieval of this data using observation, questionnaires and tests. The results of this study explain that there is a significant difference between learning using ESD-based POE modules and learning not using ESD-based POE modules. The results of the validity of a teaching module are known from the average value of the questionnaire which shows 0.9258 or in its percentage, namely 92.58% with the category very suitable for use in learning. the value of the effectiveness of a media can be seen from the results of calculations using the normality test with values ​​obtained using teaching modules and values ​​that do not use teaching modules.